Prognosis and Immune Infiltration of Chromobox Family Genes in Sarcoma - Zhou, Jian; Chen, Ziyuan; Zou, Ming; Wan, Rongjun; Wu, Tong; Luo, Yingquan; Wu, Gen; Wang, Wanchun; Liu, Tang (Frontiers in Oncology, 2021)
Background: Chomobox family genes (CBXs) were associated with multiple modifications of chromatin to inhibit target gene transcription and have been found high expressed in many cancers and serve as target gene in therapy, but the expression and prognostic value of CBXs in human sarcomas were unclear. Methods: The transcription level of CBXs was analyzed using Oncomine dataset and the differential expression of CBXs in sarcoma was reported by GEPIA dataset. We used CCLE dataset to evaluate the expression of CBXs in sarcoma cell line. The prognostic value of CBXs were analyzed using GEPIA and Kaplan-Meier plotter. Additionally, the correction between CBXs and their co-expressed genes were reported using oncomine and GEPIA dataset. DAVID was used to perform the GO function enrichment analysis of CBXs and their co-expression genes. TIMER were adopted to analyze immune cell infiltration of CBXs in patients with sarcoma. Results: HP1-α/β/γ (CBX1/3/5) and CBX4/6/8 were found overexpressed in human sarcoma, and CBXs were upregulated in almost all the sarcoma cell line. Expression of HP1-α/β/γ (CBX1/3/5) and CBX7 were associated with over survival (OS) of sarcoma, and high expression of CBX7 was related to disease-free survival (DFS). Additionally, CBX2/6/7 expression were related to recurrence-free survival (RFS). In addition, CBX family was positively correlated with infiltration of immune cells, including CD8+ T cells, CD4+ T cells, B cells, macrophages, neutrophils, and dendritic cells in sarcoma. Conclusions: The results from the present study indicated that CBXs were connected with the significance of prognostic and immunological in sarcoma, which suggest CBXs could serve as the potential biomaker of prognosis and immue infiltration in human sarcoma.